Pain Management in Functional Gastrointestinal Disorders - Antonio Vigano; Eduardo Bruera (Canadian Journal of Gastroenterology)
Pain is a common feature in functional gastrointestinal disorders (FGID). An abnormally low visceral sensory threshold, as well as a number of central, spinal and peripheral pain-modulating abnormalities, have been proposed for this syndrome. Clinical aspects of pain associated with irritable esophagus, functional dyspepsia, biliary dysmotility, inflammatory bowel syndrome and proctalgia fugax are reviewed. Because of its unclear pathophysiology, pain expression is the main target for the successful assessment and management of symptomatic FGID. The sensory, cognitive and affective components of pain intensity expression need to be addressed in the context of a good physician-patient rapport. A multidisciplinary team approach is ideal for the smaller subset of patients with severe and disabling symptoms. Although pharmacotherapy may target specific functional disorders, the role of behavioural techniques and psychotherapy appears much more important for pain management in FGID. Functional performance and quality of life improvement, rather than pain intensity, are the main therapeutic goals in these patients.